Some remarks on the images of Mary in the poetic works of selected Syriac Fathers - Lewandowicz, Janusz (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The author dedicates the text to Professor Elżbieta Umińska-Tytoń of the University of Łódź. The paper outlines poetic images concerning Mary contained in selected works of St. Ephrem the Syrian, Jacob of Sarug and in an anonymous fifth-century Hymn from the circle of Christian ancient Syriac poetry. They contain a kind of theological reflection operating with numerous comparisons, metaphors, symbols and associations, which often bring the truths of faith closer to the reader and in a more accessible way than theological treatises. The language of the works is closer to that of the liturgy. Apart from their poetic value, they bear witness to a rich Mariological tradition dating back to the first centuries. Particularly noteworthy in it are the motifs of combining the maternity and full virginity of Mary, her image as „full of grace” and mediatrix of all graces and intercessor with God.